The Influence of Educational Training and Performance Assessment on Teacher Professional Competence - Muhammad Riadhi Harly (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the effect of educational training and performance assessment on teachers' professional competence. The method used in this research is quantitative. The population in this study consists of 57 teachers from two schools, SMPN 1 and SMPN 2 Rumbio Jaya Kampar, with a sample of 50 respondents (teachers). Data collection in this study involved a questionnaire x1 with a Likert scale ranging from 1-5, x2 with a Likert scale ranging from 1-4, and y with a Likert scale ranging from 1-4. The data collection method used is Purposive Sampling. The classical assumption test uses the normality test, linearity test, and multicollinearity test. The testing of the first and second hypotheses uses multiple correlation analysis, and the joint regression coefficient test (F test) to determine the third hypothesis test. The calculations were processed using SPSS version 16. The data analysis technique used was multiple linear regression analysis. The results of this study first show that educational training has an influence on teachers' professional competence, producing a t-value of 4.370 and a t-table value of 1.676 (5% significance level, n = 50). Second, performance appraisal has an influence on teachers' professional competence, producing a t-value of 2.998. Third, the influence of educational training and performance appraisal on teachers' professional competence at SMPN 1 Tambang and SMPN 5 Tambang is 49.8% significant. It is known that the R Square value is 0.498. This means that educational training and performance assessment have an influence of 49.8% on the variable of teacher professional competence, while the remaining 50.2% is influenced by other variables not examined in this study.